Transport infrastructure in the Philippines: From plans to actual allocation - Kris A. Francisco (Philippine Institute for Development Studies (PIDS), 2024)
The Philippine government has historically underinvested in transport infrastructure until a few decades ago when the country was in a relatively more favorable financial position. The immense need to fast-track transport infrastructure investments is driven mainly by two pressure points: 1) the accumulated gap in transport infrastructure due to years of neglect; and 2) the country's sustained economic growth, further raising the demand for public infrastructure. This study provides a characterization and analysis of the government's strategy to intensify its spending on transport infrastructure, by looking at relevant statistics and public documents. It traces the government's progress in catching up with public infrastructure backlog. The analysis is done for the years 2000 to present, wherein administrations vowed to intensify government spending on physical infrastructure.
Keywords: 330; transport infrastructure; development plans; budget allocation